2008
DOI: 10.1021/ja710416h
|View full text |Cite
|
Sign up to set email alerts
|

A Quasi-Time-Resolved CryoTEM Study of the Nucleation of CaCO3under Langmuir Monolayers

Abstract: Calcium carbonate biomineralization uses complex assemblies of macromolecules that control the nucleation, growth, and positioning of the mineral with great detail. To investigate the mechanisms involved in these processes, for many years Langmuir monolayers have been used as model systems. Here, we descibe the use of cryogenic transmission electron microscopy in combination with selected area electron diffraction as a quasi-time-resolved technique to study the very early stages of this process. In this way, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
89
1
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(103 citation statements)
references
References 58 publications
8
89
1
5
Order By: Relevance
“…28 Our results in the sea urchin tooth are in agreement with the Sommerdijk group's results from synthetic calcite growth, templated by an organic Langmuir monolayer, and observed with time resolution during the transition. 29 In both systems, ACC-to-calcite is a solid-state transformation, more than one type of ACC is involved, and no bonds are broken in the process.…”
Section: Discussionmentioning
confidence: 99%
“…28 Our results in the sea urchin tooth are in agreement with the Sommerdijk group's results from synthetic calcite growth, templated by an organic Langmuir monolayer, and observed with time resolution during the transition. 29 In both systems, ACC-to-calcite is a solid-state transformation, more than one type of ACC is involved, and no bonds are broken in the process.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we used a water and alcohol mixture to stabilize the formation of aragonite to study the crystallization mechanisms using cryo‐transmission electron microscopy (cryoTEM). This technique allows the direct visualization of the early stages of the crystallization process while maintaining intermediate reaction products in their native, hydrated state 8. Utilizing this method, we demonstrate that aragonite formation in this highly supersaturated system progresses via amorphous precursor particles that aggregate to form a crystal, going through an intermediate in which semi‐oriented crystalline domains co‐exist with the amorphous phase.…”
mentioning
confidence: 97%
“…Some of them have been focused on exploring the promoting effect of matrices (templates) on the crystals' nucleation and growth (Popescu et al, 2007;Tremel et al, 2007). Several procedures have been developed, depending on the structural complexity of the templates used, such as self-assembled monolayers (Aizenberg et al, 1999;An and Cao, 2008), Langmuir monolayers (Heywood & Mann, 1994;Pichon et al, 2008), and gelatin films (Martinez-Rubi et al, 2008). Several studies have also shown that the formation of biogenic calcium carbonate structures is controlled by organic macromolecules (matrix proteins), mostly peptides and proteins, which are directly involved in regulating the nucleation, growth, and morphology of the precipitates.…”
Section: Biomimetic Formation Of Calcite Particlesmentioning
confidence: 99%